Neutrophil Redox Imbalance in Acute Coronary Syndrome - Dragojevic, Ilija M; Miric, Dijana; Kisic, Bojana; Puhalo Sladoje, Dragana; Popovic, Ljiljana; Rasic, Dragisa (Journal of Medical Biochemistry, 2025)
SummaryBackground: Oxidative stress contributes significantly to the pathogenesis of acute coronary syndrome (ACS), with neutrophils playing a pivotal role in mediating vascular injury through reactive oxygen species and myeloperoxidase (MPO)-derived oxidants. We aimed to assess the oxidative stress markers and antioxidant enzyme activities in neutrophils from ACS patients.Methods: Neutrophils were isolated from 77 ACS patients and 33 control subjects. Oxidative stress was evaluated by measuring conjugated dienes, hydroperoxides, and chloramines. Antioxidant status was assessed via non-protein and total thiol levels, and enzymatic activities of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx-1), and glutathione reductase (GR). MPO peroxidase and chlorinating activities were also quantified.Results: ACS patients exhibited significantly elevated levels of conjugated dienes (p < 0.005), chloramines (p < 0.005), thiols (p < 0.05), SOD activity (p = 0.01), and MPO chlorinating activity (p < 0.05). No significant differences were observed in catalase, GPx-1, GR, or MPO peroxidase activity. Significant correlations were found between lipid peroxidation markers and antioxidant parameters, particularly SOD and MPO chlorinating activity. Multiple regression identified SOD and chloramines as independent predictors of lipid peroxidation.Conclusion: Neutrophils from ACS patients display a disrupted redox balance characterized by enhanced lipid peroxidation, increased thiol content, and selective activation of MPO chlorination. These results underscore the relevance of neutrophil-derived redox markers as potential diagnostic tools and treatment targets in ACS.Keywords: acute coronary syndrome, neutrophils, oxidative stress
Keywords: acute coronary syndrome, neutrophils, oxidative stress